PERBANDINGAN RESPON PERTUMBUHAN BIBIT KARET AKIBAT PEMBERIAN PUPUK ANORGANIK DAN KOMPOS Azolla pinnata PADA TANAH PMK - Yusapriliani, Badriatun; Nurhayati, Nurhayati; Ratnawati Hermanto, Sarwendah (Journal of Agro Plantation (JAP), 2025)
Podzolic red-yellow soil has the potential for the development of plantation crops. Efforts to improve thefertility of Podzolic red-yellow soil include the application of both inorganic and organic fertilizers.Rubber plants are one of the important plantation crops in Indonesia. Rubber seedling is a crucial stagethat significantly determines latex production. Excessive use of inorganic fertilizers can have a negativeimpact on the environment, especially water pollution, thus it needs to be substituted with organicfertilizers. The aim of this research is to find the lowest dose of Azolla pinnata compost that providesgrowth equivalent to a dose of NPK 20 grams/polybag. This study used a completely randomized design(CRD) non-factorial with 6 treatments consisting of control: NPK 20 g/polybag, P1: Azolla pinnatacompost 100 g/polybag, P2: Azolla pinnata compost 200 g/polybag, P3: Azolla pinnata compost 300g/polybag, P4: Azolla pinnata compost 400 g/polybag, P5: Azolla pinnata compost 500 g/polybag. Eachtreatment was repeated four times. The observed parameters are seedling height, stem diameter, leaf chlorophyll, and seedling dry weight. The obtained data were analyzed using variance analysis, and ifthere was a significant effect, a difference test was conducted using LSD (Least Significant Difference) ata 5% level. The research results showed that the treatment of 200 grams/polybag was the lowest dose thatprovided growth equal to NPK 20 grams/polybag in the parameters of plant height, stem diameter,number of umbrellas, and dry weight of rubber seedlings. The use of Azolla pinnata compost startingfrom 200 grams/polybag can already replace NPK 20 grams for rubber seedling cultivation, especially inPMK soil.